STATISTICAL REGISTRATION OF INDIVIDUAL ACTION IN ATTACK FOR YOUNG VOLLEYBALL PLAYERS - Ilie-Cătălin ȘTIRBU; Cătălina Mihaela ȘTIRBU (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2016)
Through studying the degree of solicitation and effectiveness of the attack game actions, we can determine the pattern for the attack game specific to all posts inside the team; by comparing the results for sets won and those for sets lost, we can get important information regarding how and by what means we can act within practices and also official games in order to get the best possible results.